Kazakstan’s Role in the Maintenance of Security in Central Asia - BAIZAKOVA, Kuralay Irtisovna; UTEGENOVA, Ayluna Rakhmetovna; CHUKUBAYEV, Ermek Samarovich; ZHEKENOV, Duman; KARAKULOV, Yerkegali Ibraimovich (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The cooperation with the countries of Central Asia in the field of regional security has been one of the important foreign policy priorities of Kazakhstan. The threats to security in Central Asia remain to be the growing influence of Islamic radicalism, instability in Afghanistan, illicit drug trafficking, etc. This paper focuses on the role of Kazakhstan in maintaining security in the region of Central Asia. The authors examine a wide range of regional security issues and analyze the foreign policy initiatives of Kazakhstan. Kazakhstan’s initiatives on strengthening the nuclear nonproliferation regime have been analyzed in the paper. The authors analyze the relationship between Kazakhstan and organizations as NATO, OSCE, CSTO and SCO.
Keywords: Central Asia, regional security, foreign policy, Kazakhstan, diplomacy